Evaluation of Biomechanical and Chemical Properties of Gamma-Irradiated Polycaprolactone Microfilaments for Musculoskeletal Tissue Engineering Applications - Laura Rojas-Rojas; Andrea Ulloa-Fernández; Silvia Castro-Piedra; Walter Vargas-Segura; Teodolito Guillén-Girón (International Journal of Biomaterials)
An appropriate and reliable sterilization technique is crucial for tissue engineering scaffolds. Skeletal muscle scaffolds are often fabricated using microfilaments of a wide variety of polymers. One method for sterilization is 25 kGy of gamma irradiation. In addition, sterilization through irradiation should administer a dose within a specific range. Radiation directly affects the chemical and mechanical properties of scaffolds. The accuracy and effects of irradiation are often not considered during sterilization procedures; however, these are important since they provide insight on whether the sterilization procedure is reliable and reproducible. This study focused on the chemical and mechanical characterization of 25 kGy gamma-irradiated scaffold. The accuracy and uncertainty of the irradiation procedure were also obtained. X-ray diffraction (XRD) and differential scanning calorimetry (DSC) analyses were performed to determine whether the crystallinity of the polymer changed after irradiation and whether gamma rays influenced its thermal properties. The tensile parameters of the microfilaments were analyzed by comparing irradiated and nonirradiated scaffolds to determine whether gamma radiation changed their elastic behavior. Dose distribution and uncertainty were recorded with several dosimeters. The results showed that the irradiation process slightly affected the mechanical parameters of the scaffold; however, it did not modify its crystallinity or thermal properties. The irradiation was uniform, since the measured uncertainty was low. The scaffold was pathogen-free after 7 days; this meant sterilization was achieved. These results indicated that gamma-sterilized scaffolds were a promising material for use as a skeletal muscle analog material for tissue-engineering applications because they can be sterilized with gamma rays without changing their chemical structure and mechanical properties. This study provided the dose distribution measurement and uncertainty calculations for the sterilization procedure.